EFEKTIVITAS APLIKASI QUIZLET DALAM PENGUASAAN KOSAKATA BAHASA JEPANG SISWA KELAS X SMAN 9 PEKANBARU - Muhammad Arifin; Merri Silvia Basri; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study discusses the use of the Quizlet in learning Japanese vocabularyin grade 10th students of SMAN 9 Pekanbaru. The purpose of this study was to find out whetherthe Quizlet application is effective in mastering the vocabulary of grade 10th students of SMAN9 Pekanbaru and how effective the Quizlet is as a medium for learning Japanese vocabulary.The sample used in this study amounted to 34 people who were students of grade 10th Science3 SMAN 9 Pekanbaru. This research is a pre-experimental research with a research designusing one gorup pretest-posttest. Using pre-test and post-test data, the experimental classconducted a hypothesis test using a two-related sample test and the results were obtainedAsymp. Sig. (2-tailed) 0.000 > 0.05 so Hk is accepted and Ho is rejected. It can be concludedthat the Quizlet is considered effective in mastering Japanese vocabulary for grade 10thstudents of SMAN 9 Pekanbaru. To see how effective the Quizlet app is in mastering Japanesevocabulary, an N-Gain test was conducted. From the results of the N-Gain test, an N-Gainscore of 0.82 was obtained, which means that the effectiveness of the Quizlet app is consideredquite high in mastering Japanese vocabulary.Key words: Quizlet, Vocabulary, Japanese, SMAN 9 Pekanbaru